(untitled) (Fiep Bulletin - online, 2015)
The history of the curricular organization shows us that it followed paradigmatic orientations, of ontological as well as epistemological order. The organization and the development of the Physical Education’s curriculum in school, presented in the last forty years, a historical context, predominantly, based on the traditional current, in such a way that, the curriculum is being considered, by many of the involved in the educational process, a mere instrumental task, organizing a mechanical routine, following orientations of a rational and technological paradigmatic model. In that sense, Physical Education in school has been facing the need of a readequation of its role due to the deep and extensive changes in the man’s form of producing and organizing his social practice. A group of teachers felt the need to build a curriculum for the Physical Education discipline for Early Child, Elementary and Middle School levels. The objectives of this study were a) organize/construct the curriculum for Physical Education for Early Child, Elementary and Middle School; b) define the general objectives for the Physical Education discipline; c) identify the central thematic nuclei propagators of the specific knowledge to the area; c) establish selection criteria of the contents; d) build the periodization of the knowledge of the area in agreement with the scholar level. The research was participative and the ones involved in this study were Physical Education teachers that work in the University, in the Early Child, Elementary and Middle School teaching in public and particular schools of the city of Londrina. The results show that with the understandment of what is a curriculum and that with the construction and placement of the same in practice there was a professional development of the involved teachers presenting more autonomy in his school space, altering significantly and qualitatively the sense and meaning of the teachers’ work, the concept and the applicability of what is to teach Physical Education in school.